(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The trends in the communicational policies and the good practice of positioning the leading tourist destinations are aimed at the distinction of the offered products, at the certain groups and campaigns for the imposition of a brand. In this sense Bulgaria must have a clear strategy for the features and the unique offers which form the identity of a destination. Our communicational campaigns must emphasize on the specifics, on the personal experience and emotions. The purpose of this article is to prove that marketing communication is an effective way for the company to be represented, to have a good reputation, to build its image and to create the best conditions for its development.